FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KEPATUHAN DALAM MENJALANKAN PROTOKOL KESEHATAN KHUSUSNYA 3M SELAMA PANDEMI COVID-19 - Sherin Alinda Zulfa (2021)
COVID-19 is a dangerous infectious diseases because it can spread fast. prevention is needed for overcoming the spread. Indonesian government issuing various policies to prevent spread of COVID-19, one of them is healthy protocol.For achieve the objectives of the government policy, public compliance is needed. Compliance behavior is an appropriate action that adheres to a plan. This research was conducted for knowing the factor that connected with compliance behavior in running the healthy protocol especially 3M. This research is using approach Cross Sectional with 157 samples which is obtained with purposive sampling technique. This instrument research is a questionnaire that already tested the validity and reliability. This research get results that the related factors is penalty or punishment (Pvalue = 0,000). while the factor that not related is ages (Pvalue = 0,392), gender (Pvalue = 0,180), religion (Pvalue = 0,491), last education (Pvalue = 0,907), job (Pvalue = 0,862), resources (Pvalue = 0,565), socioeconomic status (Pvalue = 0,173), infected experience of covid-19 (Pvalue = 0,628), and knowledge of covid-19 (Pvalue = 0,342).